Deviation in predicted and calculated resting metabolic rates (RMR): Closing the gap. A case study from an elite British judoka (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
Judo is an Olympic Combat Sport where intense competition schedules require frequent energy deficits to enable judokas to make weight. Daily energy deficits must then be increased to match total daily energy expenditure during non-weight making phases to maintain high energy availability and ensure optimal health and performance. Failure to do this can lead judokas to maintain a long-term energy restriction, which over time has shown to be accompanied by metabolic and endocrine adaptations that can prevent further weight loss in order to conserve energy. This may then lead to a cycle of continued energy deficit by either reducing energy intake further or increasing energy expenditure leading to chronic energy deficits and in some instances putting them on the spectrum for relative energy deficit (RED-S). Deviations in predicted and calculated resting metabolic rate (RMR) has been used to measure the suppression of RMR caused by such adaptations that occur in chronically energy deficient athletes. Lower than expected RMR`s have been reported in elite female rowers and endurance athletes and correlates closely with low energy availability. This case study outlines the approach taken to help an elite female judoka showing symptoms of RED-S to increase energy intake to support performance and reduce the risks associated with frequent weight making.